A mapping of two spheres: how SEW stimulates the strategic analysis and forecast of a family firm - Adrian Ade (Management Review Quarterly, 2024)
This paper detects valuable research findings at the intersection of socioemotional wealth and strategic decision-making processes. While socioemotional wealth is a key construct in research on family firms, strategic management represents a foundational approach to strategic management processes. The systematic literature review identifies from an extensive sample, a final set of 169 journal articles using a multistep methodology. We perform an in-depth content analysis that highlights the overlap between socioemotional wealth and strategic management. One field of strategic management, namely Analysis & Forecast , offers particular potential for further research. Hence, we create construct clarity by developing five aggregated categories. These categories act as dimensions of an integrative framework with strategic analysis activities. The literature review leads to the conclusion that in previous research, each socioemotional wealth dimension influences every analysis activity but one at a time.
Keywords: A10; A12; D01; D21; D90; D91; E71; L19; L20; L21; L22; 650; Socioemotional wealth; Strategic management; Systematic literature review; Strategic analysis